Community indentification in peer-t-peer collaborative consumption services - Schnuerer, Friedrich F. (2019)
Even though collaborative consumption (CC) is gaining economic importance, research in CC is still in its infancy. Consumers’ reasons for participating have already been investigated but little research on consequences of participation has been conducted. This article examines whether interactions between customers in peer-to-peer CC services influence the willingness to coproduce service outcomes. Drawing on social exchange theory, it is proposed that this effect is mediated by consumers’ identification with the brand community. Furthermore, continuance intention in CC is introduced as a second stage moderator. In a cross-sectional study, customers of peer-to-peer accommodation sharing are surveyed. While customer-to-customer interactions were found to have a positive effect on brand community identification, brand community identification did not positively affect co-production intention. Surprisingly, the effect of brand community identification on co-production intention was negative. Moreover, continuance intention of customers did not moderate this relationship. Bearing in mind current challenges for researchers and companies, theoretical and managerial implications are discussed.